Who 'likes' public education: social media activism, middle-class parents, and education policy in Israel. Issue 6 (18th August 2018) - Avigur-Eshel, Amit; Berkovich, Izhak
Abstract: This article focuses on middle-class parent activism in the Israeli policy-making arena. In recent decades, public education governance in Israel has been moving gradually from a quasi-social democratic mode to a neoliberal one. Two e-mobilizations of middle-class parents are studied: the 'Strollers Protest' of 2011 and the 'Sardines Protest' of 2014. First, we explore how these two protests used social media to promote changes in education policies. Next, we argue that social media can be used to promote both anti-neoliberal and pro-neoliberal policies in public education. We conclude by discussing the possible implications of social media on parent activism in the policy arena.